THE IMPACT OF ADVERSITY QUOTIENT, ENTREPRENEURSHIP EDUCATION AND SELF CONFIDENCE ON ENTREPRENEURSHIP INTEREST (CASE STUDY ON STUDENTS OF FACULTY ECONOMICS AND BUSINESS UMN AL-WASHLIYAH) - Muhammad Naufal Fildza Daulay; Muthya Rahmi Darmansyah; Fitriani Tobing; Riza Fanny Meutia (CV. Radja Publika, 2025)
This study aims to determine the impact of adversity quotient, entrepreneurship education, and self confidence on entrepreneurship interest (case study on students of Faculty of Economics and Business UMN Al-Washliyah). This study is expected to be useful and provide an idea of the extent to which adversity quotient, entrepreneurial education and self confidence can affect entrepreneurship interest. To foster entrepreneurship interest in the students, they must have an adversity quotient self confidence, and the lecturers are expected to be able to provide entrepreneurial education that is able to make students interested in doing entrepreneurship activities. Through entrepreneurial education, students will open their insights about how entrepreneurial means. Respondents in this study were 87 students consisting of students of Management and Accounting Departement in Faculty of Economics and Business UMN Al-Washliyah. The research method using Multiple Linear Regression Analysis Method to perform the data analysis. The results showed that adversity quotient, entrepreneurship education and self confidence gives a positive and significant impact to cultivate the entrepreneurship interest for students of faculty economics and business UMN Al-Washliyah